2015
DOI: 10.1124/jpet.114.222125
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Visualization of the Antialbuminuric Effects of the Angiotensin-Converting Enzyme Inhibitor Enalapril

Abstract: Angiotensin-converting enzyme (ACE) inhibitors are commonly used antiproteinuric drugs. Here we assessed the effect of the ACE inhibitor enalapril on the glomerular sieving coefficient of albumin (GSC A ) using intravital multiphoton microscopy. Munich Wistar Frömter (MWF) rats were used as a model of hypertension-related glomerular lesions. Young (9-week-old) MWF rats were nonproteinuric, similar to what was observed in control Wistar rats. However, urinary albumin excretion in the MWF rats gradually increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
(63 reference statements)
0
15
0
Order By: Relevance
“…In theory this would facilitate quantitation by removing the need for background subtraction. However in actuality, setting pixels to zero decreases sensitivity and compromises the detector’s ability to detect low intensity values[19, 20]. We conducted an extensive in vitro and in vivo study on this phenomenon and demonstrated a continued reduction in detector sensitivity as more and more pixels are set to zero.…”
Section: ) Differences Between Qualitative and Intensity Based Quanmentioning
confidence: 99%
See 1 more Smart Citation
“…In theory this would facilitate quantitation by removing the need for background subtraction. However in actuality, setting pixels to zero decreases sensitivity and compromises the detector’s ability to detect low intensity values[19, 20]. We conducted an extensive in vitro and in vivo study on this phenomenon and demonstrated a continued reduction in detector sensitivity as more and more pixels are set to zero.…”
Section: ) Differences Between Qualitative and Intensity Based Quanmentioning
confidence: 99%
“…As the number of pixels at zero increases, the decrease in sensitivity becomes exponential [17]. This results in erroneous data and incorrect conclusions [16, 19, 20]. See figure 9.…”
Section: ) Differences Between Qualitative and Intensity Based Quanmentioning
confidence: 99%
“…While it might seem appropriate to adjust detector offset such that pixel values of zero are obtained in the absence of fluorescent probes (Schiessl and Castrop, 2013, Schiessl et al, 2015), such aggressive adjustment of detector offset not only eliminates detection of dim fluorescence, but it also artificially depresses estimates of fluorescence background, resulting in erroneously low measures of GSC. Accurate measures of GSC depend upon adjustment of detector offset such that positive values are obtained in regions lacking fluorescent probe, so that background levels are estimated of means of a distribution of pixel values that haven’t been artificially truncated to zero during the collection process.…”
Section: Basic Protocol 1 Glomerular Permeabilitymentioning
confidence: 99%
“…1A–C) to label the filtrate and measure the permeability of the glomerular filtration barrier to various macromolecules including dextrans, ficoll, albumin, and angiotensinogen. [2,20,2830,3235]. Importantly, this approach also helped to visualize the podocytes in negative (Fig.…”
Section: In Vivo Imaging Of the Glomerulus And The Glomerular Filtmentioning
confidence: 99%